Phenotypic and genotypic characterization of cacao cultivars (Theobroma cacao L.) from Dibulla, La Guajira, Colombia (2020)
In Sierra Nevada de Santa Marta, cacao plantations are comprised of commercial hybrid cultivars, and although native cacaos are found, they are not widely cultivated. Given the need to verify if these cacao varieties found in the Sierra region belong to the Criollo type genetic group, a phenotypic and genotypic characterization of cacao from the municipality Dibulla, La Guajira was carried out. For this, 11 cultivars were sampled in Mingueo. Phenotypic traits were evaluated using UPOV descriptors for cacao. The qualitative and quantitative parameters were compared through cluster and principal component analyses (PCA), and the quantitative variables through the non-parametric Mann-Whitney test. Molecular biology protocols were standardized, and the ITS region was sequenced to assess genetic relationships. From the sequences, groupings were carried out utilizing distance and phylogenetic methods. Finally, significant differences were found among the seeds (p = 0.01), and the white coloration of the cotyledon of the criollos or native stands out in contrast to the dark purple coloration of the hybrids. The cluster analysis, PCA, and sequence analysis groupings, showed differences between the group of native cacaos and commercial hybrids cultivated; in addition, native cacaos are related to the Criollo type group.